Morphological Parameters of Digital Subtraction Angiography 2D Image in Rupture Risk Profile of Small Intracranial Aneurysms: A Pilot Study - Hao, Ming; Ma, Jun; Huang, Qingjiu; He, Shengxue; Liang, Zheng; Wang, Chengbin (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2016)
Objective To analyze the morphological parameters of small intracranial aneurysms using two-dimensional digital subtraction angiography (DSA) and to identify their relationship with rupture risk.Methods Clinical and radiologic data from patients with DSA-confirmed small intracranial aneurysms and who received intravascular treatment were retrospectively analyzed. Morphological parameters such as maximum height, transverse diameter, aneurysm neck width, and aspect ratio (AR) were compared between patients with ruptured and unruptured aneurysms. Logistic regression analysis was performed to identify the predictors of rupture risk.Results There were no significant differences between the unruptured (n = 40) and ruptured groups (n = 34) with respect to maximum height (p = 0.087) and transverse diameter (p = 0.736). However, aneurysm neck width (p = 0.006) and AR (p < 0.001) were found to be significantly different between the groups. AR value was analyzed through the receiver operating characteristic curve, and the best AR threshold was determined to be 1.49. A stepwise multivariate analysis showed that AR was the only independent factor for rupture risk.Conclusion Two-dimensional DSA could be used to determine AR, which was an independent predictor of rupture risk of small aneurysms. Further studies with large sample sizes are needed to validate these results.
Keywords: intracranial aneurysms; digital subtraction angiography; aneurysmal subarachnoid hemorrhage; ruptured aneurysm